High performance membranes based on new 2-adamantane containing poly(aryl ether ketone) for vanadium redox flow battery applications - Zhang, Bengui; Wang, Qi; Guan, Shanshan; Weng, Zhihuan; Zhang, Enlei; Wang, Guosheng; Zhang, Zhigang; Hu, Jingwei; Zhang, Shouhai (Journal of power sources, 2018)
Membranes are essential separator components in the vanadium redox flow battery (VRFB). Many low cost and high performance membranes have been developed for this purpose, but, the chemical stability of these membranes remains a considerable challenge. Consequently, there is a pressing need to develop advanced membranes for the vanadium redox flow battery with improved performance and stability. In this reported work, the next generation of adamantane containing poly(ether ketone)s membranes that have better performance, lower cost and are more environmentally friendly were prepared and used in vanadium redox flow battery. The subject quaternized 2-adamantane containing poly(ether ketone) membranes exhibited significantly higher performance in the redox battery than a Nafion117 membrane and a N212 membrane (coulombic efficiency 98.3% vs. 96.5% (Nafion117) and 91.4% (N212)); voltage efficiency 81.9% vs. 76.7% (Nafion117) and 81.6% (N212); energy efficiency 80.5% vs. 74.0% (Nafion117) and 74.6% (N212), at 140 mA cm−2). Moreover, the resulting membranes exhibited high stability during in-situ battery cycling test and in an ex-situ chemical oxidation stability test. [Display omitted] •Advanced Q2-ADMPEK membranes are first prepared and investigated for VRFB.•VRFB with Q2-ADMPEK membranes show high battery efficiency.•Q2-ADMPEK membranes display high stability in VRFB.